Inovação tecnológica: suas relações com a estratégia e com o arranjo organizacional em empresas globais - Noffs, Sérgio Luiz (2005)
New technologies are emerging around all kind of industry and are bringing na expressive economic impact, not only for the companies, but for the entire society. The need of getting more competitiveness based on the technological opportunities represents a continuous challenge to the companies. The process that involves the technological innovation demands more than technology domain . Although it is essential, the technological competence by itself is not sufficient to promote the competitiveness. From the opportunity identification to the approval of the new product by market exists a long way to follow. On this way are faced the decisions about resources availability, destination for resources and the accomplishment of the technological process. In order to have these activities well performed, the commitment of the board is indispensable, since in that place the decisiveness and the influence power are located. Both, R&D investiments and selection of projects and technologies, take part of resource management . Not always the required technology for a technological innovation is available in the company; sometimes it can not be internally developed also. In this case, there is the need of making an evaluation about the possibility of purchasing the technology, or sharing the technology through an alliance or licensing. The technological process accomplishment demands a suitable organizational design in order to support the technological innovation. All departaments that are involved with the operation have to work harmoniously so that the possibilities of getting competitiveness advantage can be explored. The relationship between the technology team and the environment have to assure that the best technical alternatives are being considered for both parts, in accordance with the marketing point of view. A proper relationship between the development engineers and production engineers, assures the product cost and quality will colaborate with the sucess of the technological innovation. This study involves the most relevant aspects of the relations of the technological innovation with strategy and with organizational design that effect the company competitiveness, in conformity to the studied authors. As a significant result, some good elements have emerged to build the basis of a model for making analysis of technological innovation management, here named "see-saw competitiveness model". It is an analytical instrument, based on systemic vision and visual configuration. It is destined to the comprehension of how technological competences in co-ordination with strategy, can surpass market resistences against the innovation, in order to increase the competitiveness in the cases where the technological innovation is applied as a strength.